JNIS podcasts: the early part of our journey. (13th January 2016) - Hirsch, Joshua A; Fargen, Kyle; Ducruet, Andrew F; Tarr, Robert W
Abstract : Podcasts are an area of innovation in the neurointerventional space that has the potential to convey information in ways that traditional journal articles in peer-reviewed journals do not. BMJ maintains an archive of all of its podcasts on the Journal of NeuroInterventional Surgery ( JNIS ) website. We sought to analyze this early JNIS podcast experience and assess the impact of content elements and an increased presence in social media.